Social Work in Rehabilitation: Roles, Interventions, and a New Theoretical Model - Tobias Knoop; Nadja Freymüller; Thorsten Meyer-Feil; Farooq Azam Rathore (Journal of the Pakistan Medical Association, 2025)
Health related social work is a versatile profession forrehabilitation. Depending on the country andrehabilitation model, health related social work should bean important part of the rehabilitation workforce. Supportfor patients’ social and vocational participation and theorganisation of after-care are social work’s tasks.International research suggests the effectiveness of socialwork interventions for certain rehabilitation indications,but the transferability of these results to different settingsor countries is unclear. Theory can help to overcome thisproblem. Based on a qualitative dataset from a Germanhealth services research project, we developed aprogramme theory of social work in rehabilitation. Socialworkers address contextual factors through informationwork, planning work and supporting applications. Patientsare empowered to enhance the potential positive effectsof environmental factors by themselves, too. The combinedapplication of these work types by social workers results ina unique contribution in the rehabilitation workforce. Keywords: social service, disability, health servicesresearch, social workers, social determinants of health